Update on prevention and antimicrobial prophylaxis of infective endocarditis - Pavlicek-Bahlo, Maryam; Hasse, Barbara; Frank, Michelle; Conen, Anna; Papadimitriou-Olivgeris, Matthaios; Guery, Benoit; Bernheim, Alain M.; Agyeman, Philipp K.A.; Knirsch, Walter; Bornstein, Michael M.; Greutmann, Matthias; Sendi, Parham (Swiss medical weekly, 2025)
The Swiss expert group published revised guidelines on the prevention and antibiotic prophylaxis against infective endocarditis in 2021. In this viewpoint article, the group reports on their experiences two years after implementing the new prevention concept, which included information flyers and antimicrobial prophylaxis cards. Challenges included communicating the concept and indications for antimicrobial prophylaxis to both high-risk patients and providers.